THE EUROPEAN COUNCIL AND ITS ROLE IN PROMOTING AND DEFENDING HUMAN RIGHTS IN THE EUROPEAN AREA - Ion, POPESCU; Cosmin-Ionut, ENESCU (Strategii Manageriale)
The Council of Europe advocates freedom of expression and of the media, freedom of assembly, equality, and the protection of minorities. It has launched campaigns on issues such as child protection, online hate speech, and the rights of the Roma, Europe's largest minority. The Council of Europe helps member states fight corruption and terrorism and undertake necessary judicial reforms. Its group of constitutional experts, known as the Venice Commission, offers legal advice to countries throughout the world. The Council of Europe promotes human rights through international conventions, such as the Convention on Preventing and Combating Violence against Women and Domestic Violence and the Convention on Cybercrime. It monitors member states' progress in these areas and makes recommendations through independent expert monitoring bodies. All Council of Europe member states have abolished the death penalty.